FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA DI LINGKUNGAN KECAMATAN BEJI DEPOK - Edy Suryantoro; Santosa Imam Mulyono; M.B. Nani Ariani3 (Fakultas Ekonomi Universitas IBA, 2020)
This study was conducted to examine and analyze factors affecting student enterpreneurial interest In Beji Depok –West Java. This study uses a quantitative approach and The method of data analysis uses a partial least squares (PLS) model and The sample of this study used was 75 respondents. The results of this research are there is a positive influence of entrepreneurial motivation on entrepreneurial interest. the family environment variable is not significant on entrepreneurial interest. the personality variable has a significant effect on entrepreneurial interest, there is a positive influence of entrepreneurial motivation on entrepreneurial interest.